2012
DOI: 10.1007/s12011-012-9379-8
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid (JA) Acts as a Signal Molecule in LaCl3-Induced Baicalin Synthesis in Scutellaria baicalensis Seedlings

Abstract: Rare earth elements (REEs) have been widely used to increase accumulation of biomass and secondary metabolites in medicinal plants in China. However, very few studies have investigated how REEs mediate secondary metabolism synthesis in medicinal plants. Lanthanum (La), an important REE, is known to improve the accumulation of secondary metabolites in medicinal plants and is widely distributed in China. However, few studies have evaluated the signal transduction leading to La-induced secondary metabolism in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Many studies show that the effects of La on plants depend on its concentration. In plants, it has been documented that a low concentration of La can promote root organogenesis (Guo et al 2012), seed germination, and growth (Hong et al 2003), mediates secondary metabolism (Zhou et al 2012), regulates nitrogen assimilation (Huang et al 2013), and replaces calcium in the process of stomatal closure (Xue and Yang 2005). However, the excess of La has negative effects on plants by inhibiting plant growth, destroying cell structure, and disturbing metabolism (Ruíz-Herrera et al 2012, Liang and.…”
Section: mentioning
confidence: 99%
“…Many studies show that the effects of La on plants depend on its concentration. In plants, it has been documented that a low concentration of La can promote root organogenesis (Guo et al 2012), seed germination, and growth (Hong et al 2003), mediates secondary metabolism (Zhou et al 2012), regulates nitrogen assimilation (Huang et al 2013), and replaces calcium in the process of stomatal closure (Xue and Yang 2005). However, the excess of La has negative effects on plants by inhibiting plant growth, destroying cell structure, and disturbing metabolism (Ruíz-Herrera et al 2012, Liang and.…”
Section: mentioning
confidence: 99%
“…Lanthanum (La) is an important rare earth element, which can promote root organogenesis (Guo et al 2012), mediate secondary metabolism synthesis (Zhou et al 2012), and promote nitrogen metabolism (Huang et al 2013), etc. Increasing evidence has proven that La could relieve peroxidative damage in plants under many stresses, including salt and water stresses (Zhang et al 2006, Xu et al 2007, Liu et al 2016.…”
mentioning
confidence: 99%
“…However, higher doses of La may unbalance cell homeostasis by causing damage in the external membrane of the chloroplast, decreasing the concentrations of mineral nutrients in this organelle, especially those of P, Mg, K, Ca, Mn, Fe, Ni, Cu, Zn, and Mo, and disrupting Chl biosynthesis, which lead to a drastic reduction in photosynthesis, and cause lower growth or even negative impacts on plant performance (Hu et al 2016b). Additionally, REEs promoted the biosynthesis of the secondary metabolites, such as flavonoids, isoflavones, sesquiterpenoids, and benzyl ethanol glycosides in medicinal plant cells (Yuan et al 2002, Ouyang et al 2003, Huang 2006, Zhou et al 2010, Zhou et al 2012, Kovaříková et al 2019. Yuan et al (1993) found that 20 mg[La(NO3)3] kg -1 promoted the accumulation of alkaloids of Catharanthus roseus in cell cultures.…”
Section: La Increases Corm Yield and Kgmmentioning
confidence: 99%